Dynamic spatio‐temporal contribution of single β5t+ cortical epithelial precursors to the thymus medulla. Issue 4 (18th January 2016) - Mayer, Carlos E.; Žuklys, Saulius; Zhanybekova, Saule; Ohigashi, Izumi; Teh, Hong‐Ying; Sansom, Stephen N.; Shikama‐Dorn, Noriko; Hafen, Katrin; Macaulay, Iain C.; Deadman, Mary E.; Ponting, Chris P.; Takahama, Yousuke; et al.
Abstract : The thymus medulla is subject to a dramatic expansion during the first weeks of life. Using inducible TEC‐specific lineage‐tracing, Mayer et al. found that single β5t + epithelial progenitor cells located at the cortico‐medullary junction adopt a medullary TEC fate and actively contribute to this postnatal growth. Abstract : Intrathymic T‐cell development is critically dependent on cortical and medullary thymic epithelial cells (TECs). Both epithelial subsets originate during early thymus organogenesis from progenitor cells that express the thymoproteasome subunit β5t, a typical feature of cortical TECs. Using in vivo lineage fate mapping, we demonstrate in mice that β5t + TEC progenitors give rise to the medullary TEC compartment early in life but significantly limit their contribution once the medulla has completely formed. Lineage‐tracing studies at single cell resolution demonstrate for young mice that the postnatal medulla is expanded from individual β5t + cortical progenitors located at the cortico‐medullary junction. These results therefore not only define a developmental window during which the expansion of medulla is efficiently enabled by progenitors resident in the thymic cortex, but also reveal the spatio‐temporal dynamics that control the growth of the thymic medulla.